Unpacking the Challenges: An Exploration of EFL Students’ Speaking Problems - Wariyati, Wariyati; Sembiring, Yenita Br; Prawiyata, Yugi Diraga; Rosly, Rohazlyn; Heridayani, Heridayani; Dalila, Eisya (Journey: Journal of English Language and Pedagogy, 2025)
Fluency in English speaking is a vital competence for English Language Education students because it supports both academic success and future professional performance. However, many students continue to encounter difficulties in achieving oral fluency due to various internal and external factors. This study aimed to identify and analyze the factors influencing students’ challenges in speaking English fluently. The investigation focused on internal aspects such as anxiety and motivation, and external aspects including exposure to English and instructional methods. Employing a mixed-methods design, the research combined quantitative and qualitative data. A survey was administered to 56 English Language Education students to gather information about their experiences, challenges, and perceived barriers. The quantitative data were analyzed descriptively, while ten students were later interviewed to gain deeper insights into their perspectives. The results revealed that limited vocabulary, low confidence, speaking anxiety, and lack of English-speaking environments were the main obstacle affecting fluency. Most participants expressed a need for more supportive, practice-oriented learning conditions. These findings indicate that integrating interactive methods, authentic assessment, and non-threatening classroom environments can enhance students’ speaking proficiency.